Analysis of Descriptive Text Writing Skill Characteristics Based on Performance-Based Assessment for Junior High School Level - Puryanto, Edi; Kusmayanti, Nurita Bayu (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2023)
This research aims to develop a performance-based assessment model for descriptive text writing skills at the junior high school level. The success of the learning process for descriptive text writing skills in junior high school can be seen in the learning outcomes achieved by students. These learning outcomes are obtained through assessments conducted by teachers at school. However, in reality, teachers face difficulties in developing assessment tools for descriptive text writing skills. These difficulties are addressed by developing a performance-based assessment model for descriptive text writing skills. The research method used in developing the ADDIE model for skills assessment is Research and Development. The ADDIE model consists of five steps: (1) analysis; (2) design for performance-based descriptive text writing; (3) development; (4) implementation; and (5) evaluation. The results of this research include the characteristics of the assessment model for Indonesian language learning at the junior high school level.